Pengaruh Komitmen Organisasi dan Kepuasan Kerja terhadap Organizational Citizenship Behavior (OCB) - Muhammad Arsyi Akbar; Suwarsi, Sri; Shakti Firdaus, Firman (UNISBA Press, 2024)
Abstract. Employees with high organizational commitment and high job satisfaction will encourage the emergence of organizational citizenship behavior. If employees have organizational citizenship behavior, work will increase employee work productivity. Organizational citizenship behavior can be supported by organizational commitment and job satisfaction as measured by several indicators. This research was conducted at the KOPKARLA in the South Jakarta area. This research aims to determine the level of organizational commitment, job satisfaction, and organizational citizenship behavior of employees, to determine the partial and simultaneous influence. This research is included in the type of descriptive and verification research with quantitative methods. The population in this research is all employees who work at KOPKARLA, with a total of 52 employees and using saturated sampling techniques. Data was collected using a questionnaire that measured the level of organizational commitment, job satisfaction, and organizational citizenship behavior . The data analysis technique used is multiple linear regression. The results of this study show that the level of organizational commitment is included in the good category, the level of job is included in the good category. The level of organizational citizenship is included in the good category. Organizational commitment has a signifikan positive effect on organizational citizenship behavior , job satisfaction signifikan negative effect on organizational citizenship behavior , organizational commitment and job satisfaction have a positive and simultaneous effect on organizational citizenship behavior. Abstrak. Karyawan dengan komitmen organisasi yang tinggi dan kepuasan kerja yang tinggi akan mendorong munculnya perilaku organizational citizenship behavior. Perilaku organizational citizenship behavior dapat didukung oleh komitmen organisasi dan kepuasan kerja yang diukur oleh beberapa indikator. Riset ini dilakukan di KOPKARLA di Wilayah Jakarta Selatan. Penelitian ini bertujuan untuk mengtahui tingkat komitmen organisasi, kepuasan kerja, dan perilaku organizational citizenship behavior karyawan, mengetahui pengaruh secara parsial dan silmultan. Penelitian ini termasuk kedalam jenis penelitian deskriptif dan verivikatif dengan metode kuantitatif, populasi dalam penelitian ini adalah seluruhkaryawan yang bekerja di KOPKARLA, dengan jumlah total 52 karyawan dan menggunakan teknik sampling jenuh. Data dikumpulkan menggunakan kuesioner yang mengukur tingkat komitmen organisasi, kepuasan kerja, dan organizational citizenship behavior. Teknik analisis data yang digunakan adalah regresi linear berganda. Hasil penelitian ini menunjukan bahwa tingkat komitmen organisasi termasuk kedalam kategori baik, tingkat kepuasan kerja termasuk kedalam kategori baik, tingkat organizational citizenship behavior termasuk kedalam kategori baik, Komitmen organisasi berpengaruh positif siginifikan terhadap organizational citizenship behavior, kepuasan kerja berpengaruh negatif terhadap organizational citizenship behavior, komitmen organisasi dan kepuasan kerja berpengaruh positif signifikan dan simultan terhadap organizational citizenship behavior.